(untitled) (Research, Society and Development, 2024)
The gingival smile is a non-pathological condition where there is excessive exposure of the gingiva greater than 4 mm that impairs the aesthetics of two patients. It is a multifactorial condition, therefore making a correct diagnosis is essential to determine a correct treatment plan. Lip repositioning surgery is a technique that we see being implemented for the treatment of gingival sores that consists of removing a piece of mucosa from the vestibule, thus achieving a piece between the union of the mucogenic and apical lining of the upper lip muscles, curing this shape or vestibule and reducing excessive gingival exposure. The objective of this article is to understand the advances and considerations that must be taken into consideration in the implementation of the lip repositioning technique as a treatment for gum disease. Methodology: a literature review was carried out over the last 5 years by means of electronic search in the databases Science direct, Scielo, Pubmed and Google Scholar. Results: were included 22 scientific articles in which we observe the etiology, advantages and how the technique evolved over time. Conclusion: It is a widely used technique because it is minimally invasive, presents fewer postoperative complications, faster recovery and can be used in combination with other surgical or non-surgical techniques; More long-term studies are necessary, because there is also a high risk of recurrence.